Attitudes of Libyan Youth towards Political Participation and Its Role in Achieving Sustainable Development: "A Field Study" (Abhat Journal, 2025)
The current study aimed to identify the attitudes of Libyan youth towards political participation, and their role in contributing to the achievement of sustainable development in Libya. Candidacy for the presidential, legislative, and local elections, as well as membership in political parties and civil society organizations, as well as their ability to influence decisions issued by the government and females, consisting of (311) single items from different regions of Libya. The study reached a set of results, the most important of which are:1- The majority of Libyan youth agree that their discussion of local and international political issues plays an important role in the success of achieving sustainable development.2- That most of the Libyan youth will participate in the local, legislative, and presidential elections, as a means for the rise of people with developmental thinking to the government, and making public policies required for sustainable development programs in Libya. 3- Young people's attitudes were positive towards membership in political parties and civil society organizations, due to their role in educating society about the importance of sustainable development.
Keywords: Trends; political participation; Libyan youth; sustainable development